Study and Build Quality Costs Applied Research in the General Company for Grain Processing / Al-Taji Mill - Abbas Kamil Kareem; Saad Salman Al-Maaini (Journal of Madenat Alelem University College, 2022)
The research aims to demonstrate the importance of defining the reality of quality costs in economic units in the Iraqi local environment in terms of the extent to which the management of these units realizes the importance of identifying and measuring quality costs, applying quality cost systems, and the extent of interest in reducing quality costs and using financial and non-financial indicators to determine and measure quality costs, and that because of its importance in providing information that enables management to make decisions and helps in planning, control and performance evaluation in a way that enables economic units to make adjustments through the use of continuous improvement techniques and cost reduction as well as focusing on product quality and rationalizing decisions on product quality for the purpose of building a competitive advantage, which is what distinguishes the economic unit in the surrounding business environment through the optimal use of its resources that outperform its competitors, allowing it to provide products that are considered valuable by customers, which helps it maintain its market share and achieve profitability, as the research focused on a major problem faced by many units The economic situation in the Iraqi local environment due to the weak culture of the extent to which the quality of its products achieves the value of the unit as well as its neglect to identify, measure and report quality costs in special reports. The research is based on the premise that quality costs and their analysis play an important role in changing the level of product quality and help management to plan, control and make decisions. The research found the need to reconsider the cultures of economic units in the Iraqi local environment towards the quality of their products and urged them to restructure the costs of quality, which helps them to give value to the product as well as giving value to the customer.